Choosing an organizational and economic mechanism to ensure the financial security of gas distribution companies - Kateryna Oriekhova; Olena Golovko (II. Rákóczi Ferenc Kárpátaljai Magyar Főiskola, 2023)
Abstract. Changes in the natural gas market related to the implementation of the requirements of the European Union's Third Energy Package affect the financial security of gas distribution companies. Changes in the natural gas market related to the implementation of the requirements of the European Union's Third Energy Package affect the financial security of gas distribution companies. The purpose of the article is to develop a scientific and methodological approach to the selection of an organizational and economic mechanism for ensuring the financial security of gas distribution enterprises, which takes into account the combination of their status as natural monopoly entities and enterprises, and to substantiate practical recommendations for its implementation. A set of methods of scientific cognition was used, namely: the fundamental provisions of the theory of finance, probability theory and mathematical statistics, and the method of adaptive forecasting. The choice of the optimal type of organizational and economic mechanism for ensuring the financial security of gas distribution enterprises is proposed to be carried out taking into account the phased withdrawal from the financial crisis. If the type of mechanism is used effectively, the enterprise proceeds to implement a preventive mechanism; if it is ineffective, it is necessary to review the measures or proceed to the liquidation procedure; if the preventive mechanism is used effectively, the enterprise proceeds to the stabilization mechanism or a radical one. The scientific and methodological approach to the choice of an organizational and economic mechanism for ensuring the financial security of gas distribution enterprises in Ukraine has been proposed. It is aimed at consistent and targeted implementation of a set of preventive, stabilization and radical measures that enables prevention of financial risk, timely assessment and forecasting of its level, as well as development, implementation and monitoring of the relevant program. The implementation of the proposed scientific and methodological approach in the practical activities of gas distribution enterprises involves the preparation of substantive information, analytical and methodological support, which consists in a comprehensive analysis of financial security.

Резюме. Зміни на ринку природного газу, пов’язані з імплементацією вимог Третього енергетичного пакету Європейського Союзу, впливають на фінансову безпеку газорозподільних підприємств. Метою статті є розроблення науково-методичного підходу до вибору організаційно-економічного механізму забезпечення фінансової безпеки газорозподільних підприємств, який враховує поєднання їх статусу, як суб’єктів природної монополії та підприємництв, та обґрунтування практичних рекомендацій його впровадження. Використано сукупність методів наукового пізнання, а саме: фундаментальні положення теорії фінансів, теорії ймовірності та математичної статистики, та метод адаптивного прогнозування. Інформаційну базу становить річна фінансова звітність газорозподільних підприємств; наукові праці українських та зарубіжних вчених щодо забезпечення фінансової безпеки. Вибір оптимального виду організаційно-економічного механізму забезпечення фінансової безпеки газорозподільних підприємств запропоновано здійснювати з урахуванням поетапного виведення із стану фінансової кризи. За умови ефективного використання виду механізму підприємство переходить до реалізації запобіжного механізму, у разі неефективного – потрібно переглянути заходи або перейти до процедури ліквідації; у разі ефективного застосування запобіжного механізму – перехід до стабілізаційного механізму або до радикального. Запропоновано науковометодичний підхід до вибору організаційно-економічного механізму забезпечення фінансової безпеки газорозподільних підприємств України, який, на відміну від існуючих, спрямований на послідовне та цілеспрямоване здійснення комплексу заходів запобіжної, стабілізаційної та радикальної дії, що дає змогу здійснювати профілактику фінансової небезпеки, своєчасне оцінювання, прогнозування її рівня, а також розробляти, реалізовувати відповідну програму та контролювати її виконання. Впровадження запропонованого науково-методичного підходу у практичну діяльність газорозподільних підприємств передбачає на першій стадії підготовку змістовного інформаційно-аналітичного та методичного забезпечення, що полягає у здійсненні комплексного аналізу фінансової безпеки, яка залежить від впровадження системних змін, серед яких головними є перехід до нової моделі тарифоутворення та залучення нетарифних інвестицій для розвитку мереж.

Az Európai Unió Harmadik Energiacsomagja követelményeinek teljesítésével kapcsolatos változások a földgázpiacon a gázelosztó társaságok pénzügyi biztonságát érintik. A cikk célja, hogy tudományos és módszertani megközelítést dolgozzon ki a gázelosztó vállalkozások pénzügyi biztonságát szavatoló szervezeti és gazdasági mechanizmus kiválasztásához, amely figyelembe veszi a természetes monopolisztikus és vállalkozói státusz kombinációját, valamint a végrehajtására vonatkozó gyakorlati ajánlások indoklását. A kutatás során a tudományos ismeretek módszereit alkalmaztuk, nevezetesen: a pénzügyelmélet alapvető rendelkezéseit, a valószínűség-elméletet és a matematikai statisztikát, valamint az adaptív előrejelzés módszerét. Az információ alapja a gázelosztó vállalkozások éves pénzügyi kimutatásaiból, ukrán és külföldi tudósok pénzügyi biztonságának biztosításáról szóló tudományos munkáiból került ki. Javasoljuk az optimális szervezeti és gazdasági mechanizmus kiválasztását a gázelosztó vállalkozások pénzügyi biztonságának biztosítására, figyelembe véve a pénzügyi válságból való fokozatos kilépést. A mechanizmus típusának eredményes alkalmazásának feltétele mellett a vállalkozás átlép a megelőző mechanizmus megvalósításába, annak eredménytelensége esetén az intézkedések felülvizsgálata vagy a felszámolási eljárás megindítása szükséges; a biztonsági mechanizmus hatékony alkalmazása esetén – pedig szükséges áttérni a stabilizációs vagy radikális mechanizmusra. A cikk tudományos és módszertani megközelítést javasol az ukrajnai gázelosztó vállalkozások pénzügyi biztonságát szavatoló szervezeti és gazdasági mechanizmus kiválasztásához, amely a meglévőkkel ellentétben megelőző, stabilizáló és radikális intézkedések következetes és célirányos végrehajtását célozza, amely lehetővé teszi a pénzügyi veszély mértékének figyelmeztetését, időben történő felmérését és előrejelzését, valamint a megfelelő program kidolgozását, végrehajtását és nyomon követését. A javasolt tudományos és módszertani megközelítés megvalósítása a gázelosztó vállalkozások gyakorlati tevékenységében első lépésben érdemi információs, elemző és módszertani támogatás előkészítését feltételezi, amely a pénzügyi biztonság átfogó elemzésének megvalósításában áll a rendszerszintű változások végrehajtásása kapcsán, amelyek közül a legfontosabbak az új tarifaképzési modellre való átállás és a nem tarifális beruházások hálózatfejlesztési vonzása.
Вибір організаційно-економічного механізму забезпечення фінансової безпеки газорозподільних підприємств
A gázelosztó vállalkozások pénzügyi biztonságát szavatoló szervezeti és gazdasági mechanizmus kiválasztása
https://aab-economics.kmf.uz.ua/aabe/issue/view/4
Keywords: gas distribution companies; financial security; capital flow; threats; organizational and economic mechanism; adaptive forecasting